Etude De Surcreusement Des Pistes Rurales Ou Forestières, Sur Le Plateau Des Cataractes: Cas Des Routes Koubola - Kibossi Et Koubola – Bissinza (République Du Congo) - Sitou, Léonard; Milandou, Idriss M’bouka (European Scientific Journal, ESJ, 2017)
This article investigates the track overdeepening, a rare type of degradation that turns roads into trenches. He carried on two rural tracks south of Brazzaville, in the Pool Department, in the Republic of Congo, quantifying the phenomenon by the cubing method; describes the processes of formation and evolution through in situ observations; Highlights the vulnerability of the environment through the quantification of some variables representing its physical characteristics and, with the ArcGis 10.1 software, maps the phenomenon for a geo-referenced location of the main forms. Estimated at 13,724 tons of land loss on the first axis and 14,424 tons on the second road, the overcrowding is one of the forms of dramatic erosion of agricultural or forest tracks in the study area. Triggered by the bad treatment of the ruts, the processes of installation and evolution of this type of gully are favored by the sensitivity of the tracks themselves marked by apparent densities which vary between 1.7 and 1.8 g / centimeter cubic, with an average porosity (about 30%) and that of the geological formations in the clayey-clay ensemble with a high clay content (over 30%) which favors the process of overdeepening marked by the verticality or almost of the boundary walls. The mean of the erosivity index R is estimated at 6000 MJ.mm/ha.h.an, with an average annual height of 1400 mm characterizing the climatic aggressiveness of the zone and the slopes which reach and exceed the 25% , Are all aggravating factors. The prediction of this phenomenon requires a change in the method of treatment of the ruts and the stabilization of the forms already constituted and active, by that of the rolling surface and especially the walls by bio-mechanical methods.